Reconciliation of modern dichotomies: Logos and Eros - Yazıcı, Muhammet Furkan (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: This thesis gets its fundamental idea from Herbert Marcuse’s critique of modern society. His analysis concerning the petrification of modern dichotomies is our starting point. We especially focus on the modern dichotomy of Logos and Eros, in more general terms, reason and desire. According to Marcuse’s analysis, petrification of dichotomies causes us to form a relation of domination and repression between our stated faculties. And this hampers modern individuals to use their capacities in their fullest sense. As a consequence of not being able to use our capacities freely, our powers to criticize and create are degraded. After covering this analysis, as a way out from this condition of domination, we are looking Marcuse’s idea of reconciling the opposite faculties. Through his account of reconciliation, we try to discuss his accounts of aesthetics. And then we try to look at the political and social projections of his account of aesthetics. To be able to better understand Marcuse and find the starting point of his critique of modern dichotomies, we look at Friedrich Schiller in our second chapter. First off, we discuss his critique of modernity which is mainly based on modern dichotomies. After that, we try to discuss his account of aesthetics. We see that his account of Beauty and Freedom are closely related to each other and we see that those two terms stand at the center when it comes to reconciling modern dichotomies. And then, we try to understand how Schiller’s account of aesthetics is associated with his ethics and politics. On that, we see that aesthetic action gives us a better understanding of the relation between ethics, politics and aesthetics. Lastly, as a way to reconcile the opposite faculties, we look at our capacities to negate and create that are used in a creative action.

ÖZET: Bu tez, temel fikrini Herbert Marcuse’nin modern toplum eleştirisnden alıyor. Modern dikotomilerin taşlamasına ilişkin analizi bu çalışmanın başlangıç noktasıdır. Biz özellikle Logos ve Eros modern dikotomileri üzerine odaklanıyoruz, daha genel terimler ile, akıl ve arzu. Marcuse’nin analizine göre, dikotomilerin taşlaşması bu bahsettiğimiz melekelerimizin arasında baskılama ve tahakküm ilişkisi kurmamıza sebebiyet veriyor. Bu da modern bireylerin kendi kapasitelerini tam anlamıyla kullanmalarını engelliyor. Yeteneklerimizi özgürce kullanamamızın sonucu olarak eleştirel ve yaratıcı güçlerimiz azalıyor. Marcuse’nin analizini ele aldıktan sonra, bu tahakküm koşulundan bir çıkış yolu olarak, Marcuse’nin zıt melekelerimizi uzlaştırma fikrine bakıyoruz. Onun uzalaşma fikri aracılığıyla, onun estetik fikirlerini tartışmayı deniyoruz. Ve daha sonra onun estetik fikirlerinin politik ve toplumsal yansımalarına bakmayı deniyoruz. Marcuse’yi daha iyi anlayabilmek için ve modern dikotomilere yönelik eleştirisinin başlangıç noktasını bulabilmek için, ikinci bölümümüzde Friedrich Schiller’e bakıyoruz. İlk olarak, onun genel hatlarıyla modern dikotomilere dayanan modernite eleştirisini tartışıyoruz. Ondan sonra onun estetik fikirlerini tartışmaya çalışıyoruz. Görüyoruz ki Güzellik ve Özgürlük anlayışları birbiriyle yakından ilişkilidir ve modern dikotomileri uzlaştırmak söz konusu olduğunda bu iki terim merkezde durmaktadırlar. Ve daha sonra, Scihller’in estetik fikirlerinin nasıl onun etik ve politik fikirleriyle ilişkili olduğunu anlatmaya çalışıyoruz. Bununla ilgili olarak, estetik edimin bize etik, politika ve estetiğin arasındaki ilişkiye dair daha iyi bir anlayış sağladığını görüyoruz. Son olarak, zıt melekelerimizi uzalştırmanın bir yolu olarak, yaratıcı edimde kullanılan reddetme ve yaratma kapasitelerimize bakıyoruz.
Modern dikotomilerin uzlaştırılması: Logos ve Eros
Keywords: Marcuse; Schiller; Dichotomy; Reconciliation; Aesthetics; Estetik; Uzlaştırma; Dikotomi